2008
DOI: 10.1136/bjsm.2007.041541
|View full text |Cite
|
Sign up to set email alerts
|

Cricket ball injury: a cause of symptomatic muscle hernia of the leg: Figure 1

Abstract: A case of symptomatic muscle hernia of the leg in a provincial cricketer caused by a cricket ball injury is presented. It was diagnosed clinically and treated with a limited fasciotomy. However, delay in the diagnosis and treatment ended the professional career of the player. An awareness of the condition and a high index of suspicion are required to treat this condition in time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…A variety of surgical techniques have been described, ranging from fasciotomy to anatomical repair of the fascial defect, with no consensus. Described treatments include decompressive fasciotomy (16,17,20,24,39,45,46,62), direct primary fascial repair (1,11,15,20,26,36,39,41,47), tibial periosteal flap (37,63), fascial patch grafting or stripping (woven strips of fascia) using autologous fascia lata (1,2,4,15,31,33) and the use of synthetic mesh (23,30,36,40,48,52,54). Partial muscle excision has been described as a solitary treatment and as an adjunct for excessive muscle volume interfering with repair (1,14).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of surgical techniques have been described, ranging from fasciotomy to anatomical repair of the fascial defect, with no consensus. Described treatments include decompressive fasciotomy (16,17,20,24,39,45,46,62), direct primary fascial repair (1,11,15,20,26,36,39,41,47), tibial periosteal flap (37,63), fascial patch grafting or stripping (woven strips of fascia) using autologous fascia lata (1,2,4,15,31,33) and the use of synthetic mesh (23,30,36,40,48,52,54). Partial muscle excision has been described as a solitary treatment and as an adjunct for excessive muscle volume interfering with repair (1,14).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two articles reporting 43 players were found eligible and were included in the current review [ Figure 1 and Table 1 ] 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 with 62% of studies published in the past decade. Seventy-one percent of the case studies were reported from the UK and India [Figures 2 and 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, because of reports of compartment syndrome after direct repair, [5,8] this method should only be used when the defect is small and essential close postoperative follow up is assured [16]. Some authors consider the longitudinal fasciotomy the safest method of treatment [5,11,16,18,29,33]. In our case, the fascial defect was 3 × 7 cm and therefore too large for direct repair; the compartment pressure was already increased preoperatively and a direct repair would have had a high risk of postoperative compartment.…”
Section: Discussionmentioning
confidence: 99%